2012
DOI: 10.4103/0973-6042.102557
|View full text |Cite
|
Sign up to set email alerts
|

Titanium elastic stable intramedullary nailing of displaced midshaft clavicle fractures: A review of 38 cases

Abstract: Introduction:Clavicle fractures accounting for 3 to 5% of all adult fractures are usually treated non-operatively. There is an increasing trend toward their surgical fixation. The aim of our study was to investigate the outcome following titanium elastic stable intramedullary nailing (ESIN) for midshaft non-comminuted clavicle fractures with >20 mm shortening/displacement.Materials and Methods:A total of 38 patients, which met inclusion criteria, were reviewed retrospectively. There were 32 males and six femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
5
17
1
1
Order By: Relevance
“…While this finding is in concordance with previous reports [21,22,25], we were not able to reproduce the previously described lower radiation exposure for ESIN [25] as measured by fluoroscopy time or dose area product. This phenomenon could be explained by the relatively high rates of up to 71% intraoperative conversion to open fracture reduction and ESIN insertion by other studies [25,26]. Next, the complication rate of approximately 30% of the present cohort was significantly higher when compared to most of the previously reported studies [10,12,14,23,27].…”
Section: Discussioncontrasting
confidence: 62%
“…While this finding is in concordance with previous reports [21,22,25], we were not able to reproduce the previously described lower radiation exposure for ESIN [25] as measured by fluoroscopy time or dose area product. This phenomenon could be explained by the relatively high rates of up to 71% intraoperative conversion to open fracture reduction and ESIN insertion by other studies [25,26]. Next, the complication rate of approximately 30% of the present cohort was significantly higher when compared to most of the previously reported studies [10,12,14,23,27].…”
Section: Discussioncontrasting
confidence: 62%
“…Intramedullary nailing is being used successfully to treat fractures of this anatomically complex bone [11] because an intramedullary nail can be inserted with a minimally invasive technique. Closed reduction of the fracture preserves the fracture hematoma and the minimally invasive technique allows the surgeon to minimize soft-tissue dissection, thereby reducing surgical trauma, blood loss, infection, and wound complications [12]. Hill et al [7] showed that the only parameter that affects fracture healing negatively in patients with a mid-shaft clavicle fracture is shortening exceeding 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary devices behave as internal splints that maintain alignment without rigid fixation [12]. In a study comparing conservative treatment and intramedullary fixation of displaced non-comminuted fractures, Smekal et al [14] showed that clavicle shortening was significantly less with intramedullary fixation.…”
Section: Discussionmentioning
confidence: 99%
“…They are both stainless-steel intramedullary pins, which are available in multiple diameters. 19 Finally, Smekal and colleagues utilized a titanium elastic nail in the operative arm of a randomized controlled trial comparing operative fixation to nonoperative management of midshaft clavicle fractures. Both are inserted in a similar manner with the only difference being that the Rockwood pin can be inserted either medially or laterally, whereas the Hagie pin can only be inserted laterally because of an additional trocar point on the Rockwood pin.…”
Section: Discussionmentioning
confidence: 99%